Risks and Benefits of Ultrasound, Nerve Stimulation, and Their Combination for Guiding Peripheral Nerve Blocks: A Retrospective Registry Analysis. (October 2018) - Bomberg, Hagen; Wetjen, Laura; Wagenpfeil, Stefan; Schöpe, Jakob; Kessler, Paul; Wulf, Hinnerk; Wiesmann, Thomas; Standl, Thomas; Gottschalk, André; Döffert, Jens; Hering, Werner; Birnbaum, Jürgen; et al.
Abstract : BACKGROUND: Ultrasound, nerve stimulation, and their combination are all considered acceptable ways to guide peripheral nerve blocks. Which approach is most effective and associated with the fewest complications is unknown. We therefore used a large registry to analyze whether there are differences in vascular punctures, multiple skin punctures, and unintended paresthesia. METHODS: Twenty-six thousand seven hundred and thirty-three cases were extracted from the 25-center German Network for Regional Anesthesia registry between 2007 and 2016 and grouped into ultrasound-guided puncture (n = 10, 380), ultrasound combined with nerve stimulation (n=8173), and nerve stimulation alone (n = 8180). The primary outcomes of vascular puncture, multiple skin punctures, and unintended paresthesia during insertion were compared with conditional logistic regression after 1:1:1 propensity score matching. Results are presented as odds ratios and 95% CIs. RESULTS: Propensity matching successfully paired 2508 patients with ultrasound alone (24% of 10, 380 patients), 2508 patients with a combination of ultrasound/nerve stimulation (31% of 8173 patients), and 2508 patients with nerve stimulation alone (31% of 8180 patients). After matching, no variable was imbalanced (standardized differences <0.1). Compared with ultrasound guidance alone, the odds of multiple skin punctures (2.2 [1.7–2.8]; P < .001) and vascular puncture (2.7 [1.6–4.5]; P < .001) were higher with nerve stimulation alone, and the odds for unintended paresthesia were lower with nerve stimulation alone (0.3 [0.1–0.7]; P = .03). The combined use of ultrasound/nerve stimulation showed higher odds of multiple skin punctures (1.5 [1.2–1.9]; P = .001) and lower odds of unintended paresthesia (0.4 [0.2–0.8]; P = .007) compared with ultrasound alone. Comparing the combined use of ultrasound/nerve stimulation with ultrasound alone, the odds for vascular puncture (1.3 [0.7–2.2]; P = .4) did not differ significantly. Systemic toxicity of local anesthetics was not observed in any patient with ultrasound guidance alone, in 1 patient with the combined use of ultrasound and nerve stimulation, and in 1 patient with nerve stimulation alone. CONCLUSIONS: Use of ultrasound alone reduced the odds of vascular and multiple skin punctures. However, the sole use of ultrasound increases the odds of paresthesia.